Unlocking the Potential of Citrus medica L.: Antioxidant Capacity and Phenolic Profile across Peel, Pulp, and Seeds - Ana Rita Soares Mateus; João David Teixeira; Sílvia Cruz Barros; Carina Almeida; Sónia Silva; Ana Sanches-Silva (Molecules, 2024)
Citrus medica L. is a traditional citrus fruit that is rich in bioactive compounds and has the potential to be used as a natural source of food additives. This study aims to evaluate the antioxidant capacity and characterize the phenolic compounds present in the peels (including flavedo and albedo), pulp, and seeds of citron. The results showed that, compared to the other parts, the pulp had a substantially higher Antioxidant Activity Coefficient (AAC) of 168.2. The albedo and the seeds had significantly lower AAC values, while the green and yellow flavedo showed noteworthy results. O-coumaric acid was the predominant phenolic acid in all of the citron fractions; it was found in the highest concentration in albedo (37.54 µg/g FW). Flavanones and flavanols were the primary flavonoids in the pulp, peel, and seeds, with total flavonoid concentration ranging from ~9 µg/g FW in seeds to 508 µg/g FW in the pulp. This research offers significant insights into the antioxidant properties of this ancient fruit, emphasizing its potential applications as a natural source of antioxidants to be used in different applications.